A Reference Compensation Current Control strategy for Grid-Connected Inverter of Three-Phase Distributed Generators - Yunqing Zhang; Shaoru Zhang; Pingjun Wang; Lijun Wang; Ruiye Zhang; Xiaobo Liu; Lingling Liu; Yuanyuan Wu (Institute of Advanced Engineering and Science, 2014)
Renewable energy resources (RES) are being increasingly connected in distribution systems by utilizing power electronic converters. However, the extensive use of power electronics has resulted in a rise in power quality (PQ) concerns faced by the utility. A novel control strategy implementing reference compensation current was proposed in this paper. So that these grid-connected inverters can achieve maximum benefits when they were installed in 3-phase 4-wire distribution systems. The inverter is controlled to perform as a multi-function device by incorporating active power filter functionality. The inverter can thus be utilized as: 1) power converter to transfer active power from RES to the grid, and 2) load reactive power demand support; 3) current harmonics compensation at PCC; and 4) current unbalance and neutral current compensation in case of 3-phase 4-wire system. Moreover, with adequate control of grid-interfacing inverter, all the four objectives can be accomplished either individually or simultaneously. Simulation and experimental results show the validity and capability of the novel proposed control strategy. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4918